1996
DOI: 10.1068/p250095
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Local-Shape Perception

Abstract: How well do observers perceive the local shape of an object from its shaded image? We address this complex problem by rst deriving a potential representation of local solid shape, and by presenting the results of a simple psychophysical experiment. Our descriptor of local solid shape, called shape characteristic, provides a viewpoint independent continuum between hyperbolic saddle-shaped and elliptic egg-shaped points. We then study the ability of human observers to make categorical judgments of local solid sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These studies demonstratedthat such a task could be repeatedwith little variability, but unfortunately the error in terms of slant and tilt was not reported. Thirdly, perceived local solid shape has been estimated from its two components, which describe how the surface is curved and how much it is curved (Koenderink, 1990;Mamassian et al, 1996). Regarding the first component, one finds a bias to perceive small quadratic shapes as elliptic convex (Erens et al, 1993); regarding the second component, a shaded cylinder appears flatter than it actually is (Todd & Mingolla, 1983), although a relatively small Weber fraction was found in a curvature discrimination task (Johnston & Passmore, 1994a).…”
Section: Previousworkmentioning
confidence: 99%
“…These studies demonstratedthat such a task could be repeatedwith little variability, but unfortunately the error in terms of slant and tilt was not reported. Thirdly, perceived local solid shape has been estimated from its two components, which describe how the surface is curved and how much it is curved (Koenderink, 1990;Mamassian et al, 1996). Regarding the first component, one finds a bias to perceive small quadratic shapes as elliptic convex (Erens et al, 1993); regarding the second component, a shaded cylinder appears flatter than it actually is (Todd & Mingolla, 1983), although a relatively small Weber fraction was found in a curvature discrimination task (Johnston & Passmore, 1994a).…”
Section: Previousworkmentioning
confidence: 99%
“…The occluding contour of a shape (the contour that surrounds the silhouette of a shape) is a powerful cue for shape interpretation [56] which often dominates shading cues [57], and algorithms have been presented for coarsely estimating shape given contour information [58]. At the occluding contour of an object, the surface is tangent to all rays from the vantage point.…”
Section: The Occluding Contourmentioning
confidence: 99%
“…It has also been reported that other types of local shape changes are also categorically perceived (Mamassian, Kersten, & Knill, 1996). In their study, Mamassian et al asked participants to classify a specified local shape on an object surface as either hyperbolic or elliptical.…”
Section: Introductionmentioning
confidence: 99%